Studying the Effect of Changing the Stiffness Ratio of Beams and Columns of Space Frame Systems and its Vibration Period on Dynamic Response Values - ناصر, عصام; محمد, علا (Latakia University Journal -Engineering Sciences Series, 2021)
Frame models are considered one of the most important types of structural systems that are resistant to seismic loads due to their high plasticity and ability to deform before the collapse. Therefore, a number of researchers have tended to study the behavior of this type of systems to have advantages from them in increasing the bearing capacity of seismic forces. The majority of the researches that studied this aspect have dealt with simple plane frame models represented by a single space for the studied frame or a low number of storys. Due to the importance of this type of structural systems, it was necessary to expand the field of research and study the frames with more complex models in order to understand their dynamic response under the influence of an earthquake. The behavior of several different frame models has been studied with a different number of spaces and storys in this research. Stiffness ratio of beams to columns on each story has been changed and determined the dynamic response values for it. We performed a linear dynamic analysis using the response spectrum method, it was noticed that increasing in the value of stiffness ratio of beams to columns (r) led to an increase in the base shear, the overturning moment, a gradual decrease in the values of the basic period of the frame in addition to a decrease in displacement of the last roof. We found that multiple frame spaces did not affect its dynamic response values.